The Relationship Between Peripheral Vision, Visual Imagery, and Skill Performance in the Indirect Simple Attack with Direction Change Among Fencing Athletes in the Third Stage. - Isam mansoor Mohin alhameed (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The importance of the research lies in studying the relationship between peripheral vision, visual imagery, and the skill performance of the indirect simple attack with direction change. The problem of the research, through the researcher’s experience as a fencing instructor and from observing most of the lessons, was the noticeable weakness among female students, in particular, in learning the indirect simple attack with direction change. Hence, the researcher decided to study this problem by exploring the relationship between peripheral vision, visual imagery, and the skill performance of the indirect simple attack with direction change.The objectives of the research are:- To identify the levels of peripheral vision and visual imagery among third-stage female students in the College of Physical Education and Sports Sciences at Al-Ayen Iraqi Private University.- To determine the level of skill performance of the indirect simple attack with direction change among third-stage female students in the College of Physical Education and Sports Sciences at Al-Ayen Iraqi Private University.- To explore the relationship between peripheral vision, visual imagery, and the skill performance of the indirect simple attack with direction change among third-stage female students in the College of Physical Education and Sports Sciences at Al-Ayen Iraqi Private University.The researcher used the descriptive method with a correlational approach as it suits solving the problem. The research population consisted of third-stage female students in the College of Physical Education and Sports Sciences at Al-Ayen Iraqi Private University for the academic year 2025-2026, totaling 31 students. A sample of 20 students was selected, representing 64.51% of the population.Among the most important conclusions is that peripheral vision and visual imagery have a direct relationship with the evaluation of the skill performance of the indirect simple attack with direction change.